Pengaruh Work-Life Balance dan Pengembangan Karir Terhadap Motivasi Kerja Profesi Barista di Kecamatan Telanaipura Kota Jambi - Rinaldi Pratama; Putri Apria; Nurrahma Sari Putri (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
Coffee Shop Barista wants their rights as employees according to the previously agreed contract. This study aims to analyze the influence of work-life balance and career development on Barista motivation. This study is a quantitative descriptive study involving 125 Barista Coffee Shop Telanaipura. Descriptive statistical analysis is used to analyze demographic data: Work Life Balance, Career Development, and Motivation, as well as correlation and regression analysis methods. The results of the data analysis show a match between the data and the situation in the field